Chapter The Perspective of "Coup Forces," Saleh and Houthi Elements - Nevola, Luca (Springer Nature, 2020)
"From the onset of the Saada wars (2004 - 2010), the Houthis have been described as an Iranian proxy and a security threat. Ali Abdullah Saleh long deployed this Iranian narrative to obtain budgetary and military support from his long-established international allies, the United States and Saudi Arabia. Conversely, the Houthis - though admitting an Iranian influence on the ideological level - always denied receiving support from Tehran. The 2014 takeover of the capital Sanaa fundamentally reshaped the relationship between the Houthis and Saleh and their respective connections with international allies. The Houthis, on the one hand, managed to expand a previously negligible international network, establishing strong ties with regional Shiite alies and opening channels of communication with the international community. Saleh, on the other hand, embarked on a risky alliance with the Houthis to weaken his internal rivals, losing his international allies and, eventually, his own life."